Development of a flight control system using modern control techniques - Ang, Kim Siah (2009)
The objective of this research project is to develop a practical bank-to-turn (BTT) missile autopilot system. BTT steering is preferred as it is capable of increasing the lift-to-drag ratio, thus increasing the magnitude of acceleration. A survey done reviewed that the majority of today's autopilots, both in missile systems and aircraft, are designed using classical control methods. With increasingly stringent mission requirements, there is a need to develop a high performance missile autopilot by using advance control techniques.